Comprehensive Molecular Analyses of a Six-Gene Signature for Predicting Late Recurrence of Hepatocellular Carcinoma - Zhang, Yuyuan; Liu, Zaoqu; Li, Xin; Liu, Long; Wang, Libo; Han, Xinwei; Li, Zhen (Frontiers in Oncology, 2021)
A larger number of patients with stage I-III hepatocellular carcinoma (HCC) experience late recurrence (LR) after surgery. We sought to develop a novel tool to stratify patients with different LR-risk for tailoring decision-making for post-operative recurrence surveillance and therapy modalities. We retrospectively enrolled two independent public cohorts and 103 HCC tissues. Using LASSO logical analysis, a 6-gene model was developed in the TCGA-LIHC and independently validated in GSE76427. Further experimental validation using qRT-PCR assays was performed to ensure the robustness and clinical feasible of this signature. We developed a novel LR-related signature consisting of six genes. This signature was validated to be significantly associated with dismal recurrence-free survival in three cohorts TCGA-LIHC, GSE76427, and qPCR assays (HR: 2.007 [1.200-3.357], P =0.008; HR: 2.171 [1.068,4.412], P-value =0.032; HR: 3.383 [2.100,5.450], P-value <0.001). More importantly, this signature displayed robust discrimination in predicting the LR-risk, with AUCs were 0.73 (TCGA-LIHC), 0.93 (GSE76427) and 0.85 (in-house cohort). Furthermore, we deciphered the specific landscape of molecular alterations among patients in non-recurrence (NR) and LR group to analysis the mechanism contributing to LR. For high-risk group, we also identified several potential drugs with specific sensitivity to high and low-risk groups, which is vital to improve prognosis of LR-HCC after surgery. We discovered and experimental validated a novel gene signature with powerful performance for identifying patients at high LR-risk in stage I-III HCC.